Spinal embryonal rhabdomyosarcoma with multiple distant metastasis: a case report - Gayatri Autkar; Harshitha Shetty; Swapnil Moharkar (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Rhabdomyosarcoma is the most common soft-tissue sarcoma in children and is usually found in the head, neck, orbit, genitourinary tracts and extremities. An unusual pattern is diffuse bone marrow involvement by rhabdomyosarcoma. In such cases, the initial presentation of patients is similar to haematological malignancy like leukaemia, especially when the primary tumour is not evident. This pattern is rare; however, awareness of this pattern is important for radiologists for appropriate early diagnosis and treatment. Rhabdomyosarcoma involving the spine is extremely rare with very few case reports available in the literature. Case presentation We present a case of a seven-year-old boy presenting with subacute paraplegia associated with high-grade fever following a genitourinary surgery. The differential diagnosis of post-surgical complications like infective spondylodiscitis, epidural abscess and transverse myelitis were considered clinically. Magnetic resonance imaging of the spine revealed heterogenous enhancement of the bone marrow of the vertebrae and the pelvic bones along with paravertebral and epidural enhancing soft tissues and the most likely differential diagnosis was leukaemia/lymphoma. Histopathology and immunohistochemistry of the soft tissue revealed an embryonal rhabdomyosarcoma. [1⁸F] Fluorodeoxyglucose PET-CT revealed extensive marrow lesions in the axial and appendicular skeleton. In view of extensive metastatic disease, the patient was given palliative therapy. The unusual primary site and presentation with multiple metastasis makes this case worth reporting. Conclusion Spinal or bone marrow involvement in rhabdomyosarcoma is uncommon, and it provides a diagnostic challenge in view of the non-specific signs and symptoms. Haematological malignancy is often the primary diagnosis made clinically and on imaging. Spinal or bone marrow involvement in rhabdomyosarcoma implies an overall poor prognosis of the patient. Multimodality therapy is the mainstay of management in spinal rhabdomyosarcoma, which includes surgery, chemotherapy, radiotherapy and palliative treatment in cases of extensive metastasis.